2018
DOI: 10.1159/000489445
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Telocytes Attenuates Unilateral Ureter Obstruction-Induced Renal Fibrosis in Rats

Abstract: Background/Aims: Previous studies imply that telocytes may have a protective effect on fibrosis in various organs, including the liver, colon, and heart. The effect of telocytes on renal fibrosis remains unknown. Herein, this study was designed to investigate the effect of telocytes on renal fibrosis and the potential mechanisms involved. Methods: In a unilateral ureteral obstruction (UUO)-induced renal fibrosis model, telocytes were injected via the tail vein every other day for 10 days. The degree of renal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
(44 reference statements)
0
23
0
Order By: Relevance
“…In greater detail, Olga simionescu and colleagues demonstrated that telocytes maintained in close contact with mast cells, macrophages and mononuclear cells by their long telopode and an apoptotic telocyte with condensed chromatin has been found in the vicinity of a dendritic cell in psoriasis . Although a few studies have reported the function of telocytes, little is known about the relationship between telocytes and other cells. We found that the level of iNOS was significantly increased after TLR2 activation (Figure C,), suggesting that activated telocytes had enhanced the ability of immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…In greater detail, Olga simionescu and colleagues demonstrated that telocytes maintained in close contact with mast cells, macrophages and mononuclear cells by their long telopode and an apoptotic telocyte with condensed chromatin has been found in the vicinity of a dendritic cell in psoriasis . Although a few studies have reported the function of telocytes, little is known about the relationship between telocytes and other cells. We found that the level of iNOS was significantly increased after TLR2 activation (Figure C,), suggesting that activated telocytes had enhanced the ability of immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Associated pathologies/dysfunctions Kidneys Renal cortex (Qi et al, 2012), Interstitium and renal capsule (Zheng et al, 2012) Macrophages blood vessels (Zheng et al, 2012) Erythropoiesis stromal tissue (Imeri et al, 2019), Organization/maintenance (Zheng et al, 2012) Myxomas (Mandache & Penescu, 2015), Ischemia (Li et al, 2014), Renal fibrosis (Zheng et al, 2018) Renal Pelvis Interstitium (Gevaert et al, 2012) Nerve endings blood vessels (Gevaert et al, 2012) ER signaling pathway (Gevaert et al, 2012) Unclear Ureters Lamina Propria, Sheath of Waldeyer (Rusu et al, 2018b) Epithelial cells nerve endings blood vessels (Rusu et al, 2018b;Zheng et al, 2012) Stem/progenitor niche (Dobra et al, 2018), Stromal tissue organization/maintenance (Zheng et al, 2012) Hydronephrosis (Wolnicki et al, 2019)…”
Section: Possible Functionsmentioning
confidence: 99%
“…However, this protective effect occurs through an inflammation‐independent pathway, possibly due to the production of growth factors capable of promoting the proliferation of epithelial cells in the renal tubules (Li et al, 2014). In cases of fibrosis‐induced experiments, there is evidence that the transplantation of telocytes could attenuate characteristic stromal changes, downregulating the proliferation of myofibroblasts, as well as decreasing serum levels of TGFβ1 and increasing levels of hepatocyte growth factor (Zheng et al, 2018). This factor prevents epithelial cell death and also enhances regeneration of renal tissue after injury (Matsumoto & Nakamura, 2001).…”
Section: Male Urinary Tractmentioning
confidence: 99%
“…Western blot analysis was performed as described previously (29). Briefly, the total protein was extracted from kidney tissue samples or cultured cells (15 mg each) and separated using electrophoresis.…”
Section: Western Blot Analysismentioning
confidence: 99%